Modulation of CD14 and TLR4⋅MD‐2 Activities by a Synthetic Lipid A Mimetic. Issue 2 (12th December 2013) - Cighetti, Roberto; Ciaramelli, Carlotta; Sestito, Stefania Enza; Zanoni, Ivan; Kubik, Łukasz; Ardá‐Freire, Ana; Calabrese, Valentina; Granucci, Francesca; Jerala, Roman; Martín‐Santamaría, Sonsoles; Jiménez‐Barbero, Jesus; Peri, Francesco
Abstract Monosaccharide lipid A mimetics based on a glucosamine core linked to two fatty acid chains and bearing one or two phosphate groups have been synthesized. Compounds 1 and 2, each with one phosphate group, were practically inactive in inhibiting LPS‐induced TLR4 signaling and cytokine production in HEK‐blue cells and murine macrophages, but compound 3, with two phosphate groups, was found to be active in efficiently inhibiting TLR4 signal in both cell types. The direct interaction between compound 3 and the MD‐2 coreceptor was investigated by NMR spectroscopy and molecular modeling/docking analysis. This compound also interacts directly with the CD14 receptor, stimulating its internalization by endocytosis. Experiments on macrophages show that the effect on CD14 reinforces the activity on MD‐2⋅TLR4 because compound 3's activity is higher when CD14 is important for TLR4 signaling (i.e., at low LPS concentration). The dual targeting of MD‐2 and CD14, accompanied by good solubility in water and lack of toxicity, suggests the use of monosaccharide 3 as a lead compound for the development of drugs directed against TLR4related syndromes.